Implementation of ESP in Secondary Education Curricula: Challenges and Opportunities - A Literature Review - Rahman Efendi; Satriani Satriani; Rosmiati Hamma; Amaluddin Amaluddin (Universitas Muhammadiyah Enrekang, 2024)
English for Specific Purposes (ESP) is an approach to English language teaching that focuses on the specific needs of learners in professional and academic contexts. The implementation of ESP in the secondary education curriculum can provide significant advantages in preparing students for specific communication demands in the future. This article aims to explore the challenges and opportunities in the implementation of ESP in secondary education curriculum through a comprehensive literature review. The reviewed literature was selected based on the criteria of publication date, relevance, research type, and reliable source. Data were collected from various academic databases such as Scientific research, Science Direct, Wiley Online library, Google Scholar, Internet TESL Journal, Open edition journals and etc. The data analysis process involved thematic coding and synthesizing information from the selected articles. The findings show that ESP implementation faces major challenges such as a shortage of trained teachers, limited educational resources, and resistance to curriculum change. However, there are great opportunities that can be exploited, including the utilization of digital technology, international collaboration, and the integration of ESP with the national curriculum. Overcoming these challenges requires continuous teacher training programs, development of technology-based learning materials, and inclusive approaches in curriculum planning. International collaboration can also provide valuable practical experience for students and teachers. The implementation of ESP in secondary education has great potential to improve students' English competence in specific contexts. Further research is needed to develop effective teacher training programs, innovative learning materials, and adaptive curriculum implementation strategies. Keywords: English for Specific Purposes (ESP), secondary education, curriculum, challenges, opportunities, literature review.